COMPARATIVE STUDY ABOUT HOSPITAL BUILDING DESIGN WITH INTERMEDIATE MOMENT FRAME SYSTEM AND DUAL SYSTEM - CAROLINA SIMANJUNTAK (NIM. 15007047); Dosen Pembimbing : Dr. Ir. Saptahari M. Soegiri Poetra, RINI
Most areas of Indonesia is a region which has high vulnerability to earthquakes. In sloving the structural problems of the earthquake in Indonesia, some elements of a structure must be designed so as to be able to withstand lateral forces (earthquake loads) that occur. In general, the system structure divided into two parts, namely bearer moment frame system and structural wall systems. This thesis is redesigned hospital re-building structure using open-frame system and compared with the existing design which is built on the ground that the dual system. Objectives to be achieved is to get the value of drift whose value is less than 1% of the height of the building (the immediate occupancy performance level). The results obtained are building with dual system is much less expensive judging by the amount of reinforcement used. From the pushover, the ductility of the structure of SRPM twice greater than the dual system, but the value of the shear load on the system doubles to 50% larger than the structure of SRPM. As for the selection of each type of structure has advantages that are tailored to the needs of the owner